Pengaruh Tingkat Pendidikan dan Pengalaman Kerja terhadap Kepatuhan Pegawai dalam Penyelesaian Tindak Lanjut Hasil Pengawasan Inspektorat : (Studi pada Unit Kerja Pemerintah Kabupaten Gorontalo Utara) - Nuraisa Pulunama; Gaffar Gaffar; Mattoasi Mattoasi (Al-Buhuts, 2025)
This study aims to determine the effect of education level, employee work experience on employee compliance in completing follow-Up on audit findings in the North Gorontalo Regency government work unit. The study used a quantitative approach with descriptive methods. The sample in this study were 44 respondents. Data collection using questionnaires and documentation and data analysis techniques using descriptive analysis, instrument testing, multiple linear regression analysis in testing hypotheses. The results of data analysis, it shows that; The level of education has a positive influence on employee compliance in completing follow-up supervision results; work experience has a positive and significant effect on employee compliance in completing follow-up supervision results, and The combination of education level and work experience shows a positive influence on employee compliance in completing follow-up supervision results